Developing a New Two-Step Protocol to Generate Functional Hepatocytes from Wharton's Jelly-Derived Mesenchymal Stem Cells under Hypoxic Condition - Patcharee Prasajak; Wilairat Leeanansaksiri (Hindawi Limited, 2013)
The shortage of donor livers and hepatocytes is a major limitation of liver transplantation. Thus, generation of hepatocyte-like cells may provide alternative choice for therapeutic applications. In this study, we developed a new method to establish hepatocytes from Wharton's jelly-derived mesenchymal stem cells (WJ-MSCs) cell lines named WJMSCs-SUT1 and WJMSCs-SUT2 under hypoxic condition. This new method could rapidly drive both WJ-MSCs cell lines into hepatic lineage within 18 days. The achievement of hepatogenic differentiation was confirmed by the characterization of both phenotypes and functions. More than 80% MSCs-derived hepatocyte-like cells (MSCDHCs) achieved functional hepatocytes including hepatic marker expressions both at gene and protein levels, glycogen storage, low-density lipoprotein uptake, urea production, and albumin secretion. This study highlights the establishment of new hepatogenic induction protocol under hypoxic condition in order to mimic hypoxic microenvironment in typical cell physiology. In conclusion, we present a simple, high-efficiency, and time saving protocol for the generation of functional hepatocyte-like cells from WJ-MSCs in hypoxic condition. The achievement of this method may overcome the limitation of donor hepatocytes and provides a new avenue for therapeutic value in cell-based therapy for life-threatening liver diseases, regenerative medicine, toxicity testing for pharmacological drug screening, and other medical related applications.